2017
DOI: 10.1016/j.jnggs.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Study on the lower limits of petrophysical parameters of the Upper Paleozoic tight sandstone gas reservoirs in the Ordos Basin, China

Abstract: There hasn't been a clear understanding of the lower limits of petrophysical parameters of tight sandstone gas reservoirs so far. However, it is an important question directly related to exploration and development strategies. Research methods of the lower limits of petrophysical parameters are reviewed. The new minimum flow pore throat radius method is used to determine the lower limit of flow pore throat radius. The relative permeability curve method, irreducible water saturation method, and testing method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…There was good correlation between porosity and permeability. Permeability increased with an increase of porosity [29,30], which showed that permeability is mainly controlled by reservoir pores, but not by fractures or cleats. On the basis of mercury injection testing analysis, displacement pressure was found to be generally high, in the range 0.1-4.97 MPa; the maximal pore throat radius was 0.25 to 181 µm, mostly 0.25 to 1.5 µm, with an average of 14.14 µm; the median capillary pressure was 0.1096 to 197 MPa, mostly 3 to 50 MPa; the median pore throat radius was 0.03 to 2.24 µm, with an average of 0.4 µm; the pore throat was relatively smaller.…”
Section: Porosity Permeability and Reservoir Pressurementioning
confidence: 90%
See 1 more Smart Citation
“…There was good correlation between porosity and permeability. Permeability increased with an increase of porosity [29,30], which showed that permeability is mainly controlled by reservoir pores, but not by fractures or cleats. On the basis of mercury injection testing analysis, displacement pressure was found to be generally high, in the range 0.1-4.97 MPa; the maximal pore throat radius was 0.25 to 181 µm, mostly 0.25 to 1.5 µm, with an average of 14.14 µm; the median capillary pressure was 0.1096 to 197 MPa, mostly 3 to 50 MPa; the median pore throat radius was 0.03 to 2.24 µm, with an average of 0.4 µm; the pore throat was relatively smaller.…”
Section: Porosity Permeability and Reservoir Pressurementioning
confidence: 90%
“…The original reservoirs were filled with water before gas charging in geological setting. Gas generates in source rocks and migrates into the reservoirs, and water is substituted by gas in reservoirs [28,29]. The characteristics of gas migration and accumulation were investigated by the experiments of gas displacing water.…”
Section: Methodsmentioning
confidence: 99%
“…Tight sandstone gas and shale gas reservoirs comprise ultratight porous media with pore sizes at the micrometer to nanometer scale, and the intrinsic matrix permeability and porosity are extremely low. China has abundant unconventional natural gas reserves; among these, the development of the tight sandstone gas reservoirs has the most practical significance because of their large size . Zou et al indicated that tight sandstone gas reservoirs in China have a pore throat radius of 25‐700 nm and intrinsic matrix permeability of less than 0.1 × 10 −3 µm 2 under overburden pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The Ordos Basin in central China represents the largest oil and gas production region in China (Cui et al, 2017;Hao et al, 2017) and has therefore been the focus of many previous studies. Recent research has identified a new tight carbonate gas exploration field within the Middle Ordovician Majiagou Formation in the east of the basin, specifically within weathering crust layers in the first and second submembers of the fifth member (herein referred to as Ma 5 1 þ 2 ; Wei et al, 2017aWei et al, , 2017b.…”
Section: Introductionmentioning
confidence: 99%